Analysis of Digitalization on Government Governance and Government Internal Control System (Study At Lamongan Regency) - Rini Apriani; Ajeng Rahmadini; Alvira Khoirunnisa; Rimi Gusliana Mais (Labkat Press KA FTIK UNIKOM, 2025)
This study aims to examine the influence of digitalization, good governance principles, and the effectiveness of the Government Internal Control System (GICS) on the quality of the Lamongan Regency Local Government Financial Statements (LKPD). Although Lamongan Regency received an Unqualified Opinion (WTP) from the Audit Board of Indonesia (BPK) in 2023, audit findings still revealed weaknesses in GICS implementation and regulatory non-compliance, particularly in budgeting, expenditure control, and financial report verification. The data for this study were obtained through documentation of financial statements and audit reports sourced from the official local government website. The analysis results indicate that good governance principles-such as accountability, transparency, and public participation-have been implemented but have not had a significant impact on financial report quality at Lamongan Regency. Meanwhile, GICS weaknesses are a key factor affecting report quality, although they did not materially affect the audit opinion. This study recommends that the local government enhance human resource capacity, optimize internal supervisory functions, and strengthen the risk evaluation system to support more accountable and transparent financial management. Strengthening governance and internal control is essential not only in financial reporting but also in building a clean and professional governance culture across all levels of local government of Lamongan Regency.